Влияние нарушений мочеиспускания на качество жизни при урогенитальной форме диабетической автономной нейропатии у пациенток с сахарным диабетом 1 и 2 типов = Influence of urination disorders on quality of life in the urogenital form of diabetic autonomic neuropathy in patients with diabetes mellitus type 1 and 2 - N. A. Kravchun; E. Y. Tkachuk; V. V. Shuhtin; V. S. Goydyk (Kazimierz Wielki University, 2016)
Kravchun N. A., Tkachuk E. Y., Shuhtin V. V., Goydyk V. S. Влияние нарушений мочеиспускания на качество жизни при урогенитальной форме диабетической автономной нейропатии у пациенток с сахарным диабетом 1 и 2 типов = Influence of urination disorders on quality of life in the urogenital form of diabetic autonomic neuropathy in patients with diabetes mellitus type 1 and 2. Journal of Education, Health and Sport. 2016;6(9):682-690. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159072 http://ojs.ukw.edu.pl/index.php/johs/article/view/3897         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Влияние нарушений мочеиспускания на качество жизни при урогенитальной форме диабетической автономной нейропатии у пациенток с сахарным диабетом 1 и 2 типов   Н. А. Кравчун, Е. Ю. Ткачук В. В. Шухтин, В. С. Гойдык   ГУ «Институт проблем эндокринной патологии имени В.Я. Данилевского НАМН Украины», г.Харьков; Областная клиническая больница - Центр экстренной медицинской помощи и медицины катастроф, г.Харьков Украинский научно-исследовательский институт медицины транспорта МЗ Украины, Одесса   Резюме Изучено влияние нарушений мочеиспускания на качество жизни при урогенитальной форме диабетической автономной нейропатии у 195 пациенток с сахарным диабетом 1 и 2 типов. Оценка качества жизни проводилась при помощи Short Form Medical Outcomes Study (SF-36), а для выявления нарушения мочеиспускания использовалась разработанная нами шкала-опросник при сахарном диабете. Установлено, что в зависимости от степени тяжести нарушений мочеиспускания качество жизни у пациенток с указанной патологией достоверно ухудшается, психический компонент качества жизни угнетается в большей степени. Ключевые слова: сахарный диабет, урогенитальная форма, нарушение мочеиспускания, качество жизни, SF-36.             Influence of urination disorders on quality of life in the urogenital form of diabetic autonomic neuropathy in patients with diabetes mellitus type 1 and 2   N. A. Kravchun, E. Y. Tkachuk, V. V. Shuhtin, V. S. Goydyk     SI "V. Danilevsky Institute for Endocrine Pathology Problems named of the NAMS of Ukraine", Kharkiv; Regional Clinical Hospital - Centre of emergency medical care and emergency medicine, Kharkiv Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine   Summary Was studied effect of voiding disorders on quality of life in the urogenital form of diabetic autonomic neuropathy in 195 patients with diabetes mellitus type 1 and 2. Quality of life assessment was performed using the Short Form Medical Outcomes Study (SF-36), and to detect urination disorders used the scale - a questionnaire we have developed for patients with diabetes. It was found that, depending on the severity of urinary disorders quality of life of patients with this pathology significantly worsens the mental component of quality of life is inhibited to a greater extent. Key words: type 1 and 2 diabetes mellitus, the urogenital form of diabetic autonomic neuropathy, urination disorders, quality of life, SF-36.                     Вплив порушень сечовипускання на якість життя при урогенітальній формі діабетичної автономної нейропатії у пацієнток з цукровим діабетом 1 і 2 типів   Н. О. Кравчун, О. Ю. Ткачук. В. В. Шухтін, В. С. Гойдик   ДУ «Інститут проблем ендокринної патології імені В.Я. Данилевського НАМН України», м. Харків; Обласна клінічна лікарня - Центр екстреної медичної допомоги та медицини катастроф, м. Харків. Український науково-дослідний інститут медицини транспорту МОЗ України, Одеса     Резюме Вивчено вплив порушень сечовипускання на якість життя при урогенітальній формі діабетичної автономної нейропатії у 195 пацієнток з цукровим діабетом 1 і 2 типів. Оцінка якості життя проводилась за допомогою Short Form Medical Outcomes Study (SF-36), а для виявлення порушень сечовипускання використовувалась розроблена нами шкала-опитувальник при цукровому діабеті. Встановлено, що в залежності від ступеня тяжкості порушень сечовипускання якість життя у пацієнток із зазначеною патологією достовірно погіршується, психічний компонент якості життя пригнічується більшою мірою. Ключові слова: цукровий діабет 1 і 2 типу, урогенітальна форма діабетичної автономної нейропатії, порушення сечовипускання, якість життя, SF-36.